A meta-analysis and systematic review of reactivity to judgements of learning. Issue 6 (3rd July 2018) - Double, Kit S.; Birney, Damian P.; Walker, Sarah A.
ABSTRACT: Judgements of learning (JoL) are often used in memory research as a means for assessing an individual's metacognitive beliefs about their learning. JoL have been shown to reliably predict performance as well as learning behaviours and decisions . Participants may, however, modify their behaviour in response to performing JoL. There has, however, been little consensus as to the reliability and direction of the effect. We report on a meta-analyses that assesses the evidence that memory performance is reactive to JoL. The results indicate that overall providing JoL does not have a significant effect on memory performance ( g  = 0.054, 95% CI −0.027 to 0.135). However, sub-groups analysis showed that this effect depends on the nature of the stimuli to be recalled, with moderate positive reactivity observed for related word pairs ( g  = 0.323, 95% CI 0.083 to 0.563) and word lists ( g  = 0.384, 95% CI 0.146 to 0.622) but no reactivity when pairs were unrelated or a mixture of related and unrelated pairs. These results indicate that researchers should be aware that eliciting JoL may well influence participants' underlying encoding processes, especially when using related word pairs or word lists.